Animated video education on the level of knowledge of Gastroesophageal Reflux Disease (GERD) in teenager - Nasution, Nurromsyah; Rahmadaningsih, Dinda; Satria, Orita (Science Midwifery, 2024)
Background: GERD is one of the most frequently encountered and currently experienced problems an increase in prevalence every year. Apart from an unhealthy lifestyle, lack of knowledge can also be a risk factor for teenagers experiencing GERD. With the sophistication of technology, we can easily increase our knowledge with various media, one of which is animated video media. This type of research is quantitative research using a quasi-experiment design with one group pre-test post-test. This research collected data at SMA N 2 Meulaboh. The sample in this study was 210 respondents using probability sampling techniques. Data analysis used the Wilcoxon test. The research results found that applying animated videos could influence the level of knowledge about GERD in adolescents with a P value of 0.000. Research conclusion: There is an influence of animated videos on the level of knowledge of GERD in adolescents.